مدى مساهمة الرياضة المدرسية في إكتشاف المواهب الرياضية في الطور المتوسط من 11- 15 سنة - بن شيخ, زهير (Institut d'Éducation Physique et Sportive - Mostaganem 2024/2025, 2025)
ملخص الدراسة باللغة العربية هدفت هذه الدراسة إلى التعرف على مدى تنظيم الرياضة المدرسية ضمن إطار يتيح اكتشاف المواهب الرياضية، ودور رابطة الرياضة المدرسية، والتنسيق مع النوادي الرياضية. أُجريت الدراسة على عينة من 55 أستاذًا باستخدام استبيان إلكتروني، وتوصلت إلى أن التنظيم الحالي للرياضة المدرسية غير كافٍ، ومساهمة الرابطة محدودة، والتنسيق مع النوادي ضعيف. وعليه، أوصت الدراسة بضرورة إعادة هيكلة الرياضة المدرسية، وتفعيل دور الرابطة، وتعزيز التنسيق مع النوادي. // // // // // This study aimed to assess how school sports are organized to discover athletic talents, as well as the role of the School Sports Association and its coordination with sports clubs. The study was conducted on a sample of 55 physical education teachers using an online questionnaire. The findings revealed that the current organization is insufficient, the association's role is limited, and coordination with clubs is weak. Therefore, the study recommends restructuring school sports, enhancing the association’s role, and improving collaboration with sports clubs.
MES-2025-17
Keywords: : الرياضة المدرسية- المواهب الرياضية- تلاميذ الطور المتوسط (15-11 سنة)- أساتذة التربية البدنية والرياضية // // School sports- sports talents- middle school pupils (ages 11–15)- physical education teachers